The Effects of Electoral Institutions in Rwanda: Why Proportional Representation Supports the Authoritarian Regime - Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2009)
While much has been written about the special design of Rwanda's judiciary in order to handle the aftermath of the genocide in 1994, other institutional actions resulting from the 2003 constitution have rarely been addressed in research. However, the second (partial) par-liamentary elections in September 2008 revealed some of the implications which the care-fully designed electoral system has for Rwanda's political development. As a starting point, the paper emphasises the need to link the debates on institutional design in divided societies with elections in authoritarian regimes. Under different regime types, 'institutional engineers' may pursue different goals. The paper concludes that in the case of Rwanda propor-tional representation (PR) has been implemented to support undemocratic goals. PR limits the local accountability of politicians in a political environment in which the government is not controlled by a democratic opposition. Thus, Rwanda's current PR system facilitates the maintenance of authoritarian power in the country, whereas small constituencies would es-tablish closer links between the local populations and their representatives. – – Während das besondere institutionelle Design der ruandischen Justiz, das dazu dienen soll, die Folgen des Völkermords von 1994 zu bewältigen, Gegenstand vieler Untersuchungen ist, wurden andere institutionelle Reaktionen der Verfassung von 2003 nur sehr selten betrachtet. Die zweiten (partiellen) Parlamentswahlen im September 2008 haben jedoch einige Folgen des sorgfältig entworfenen Wahlsystems des Landes für dessen politische Entwicklung erkennen lassen. Für die Analyse dieser Wahlen führt der Verfasser dieses Beitrags die Literatur zu Institutional Design in konfliktträchtigen Gesellschaften und zu Wahlen in autoritären Regimen zusammen und wertet sie aus. Dadurch kommt er zu folgendem Schluss: Zumindest im politischen Kontext Ruandas, in dem die Regierung nicht von einer demokrati-schen Opposition kontrolliert wird, weil diese entweder erfolgreich kooptiert oder von politischer Einflussnahme ausgeschlossen wurde, schränken Verhältniswahlsysteme mit großen Wahlkreisen die Möglichkeit ein, Politiker lokal für ihr Handeln verantwortlich zu machen. Daher trägt das ruandische Wahlsystem tendenziell dazu bei, autoritäre Herrschaft auf-rechtzuerhalten. Hingegen wären kleinere Wahlkreise, die mit der lokalen Bevölkerung enger verbunden sind, besser geeignet, eine kulturell und historisch angepasste Grundlage für mehr politische Verantwortlichkeit gewählter Politiker herzustellen.
Keywords: 300; Rwanda; electoral authoritarianism; electoral system; parliament; constituency size